Complete response to disitamab vedotin in HER2-low metastatic endometrial carcinoma: a case report and review of the literature - Feng, Hu; Bi, Shasha; Sun, Shanshan; Yang, Hongbo; Zhou, Haoxing; Mao, Jingjing (Frontiers in Oncology, 2024)
Endometrial cancer (EC) is one of the most common gynecologic malignancies with increasing morbidity. The prognosis for patients diagnosed with early-stage EC remains favorable; however, for patients with recurrent or metastatic EC, the prognosis is poor and treatment options, until recently, are limited. Antibody drug conjugates (ADCs) represent innovative strategies in cancer treatment; however, there are less investigations regarding their efficacy in EC. This report describes an EC case with low human epidermal growth factor receptor 2 (HER2) immunohistochemistry (IHC) expression score (IHC 2+) that experienced recurrent metastasis in the abdominal and peritoneal following post-surgical chemotherapy and radiotherapy. Subsequently, the commencement of HER2-targeted ADC, disitamab vedotin (RC48; 2.5 mg/kg), administered intravenously every two weeks, was initiated. The tumor lesions shrunk markedly after three cycles of treatment and disappeared by the completion of ten cycles of therapy. The patient is still in remission at present. The current findings imply the potential efficacy of HER2-targeted ADCs for patients with HER2-low metastatic EC.